2011
DOI: 10.2174/1876520301104010001
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Punch Density and Fiber Blends on Thermal Conductivity on Nonwoven

Abstract: One of the major applications for nonwoven fibrous system is as thermal insulation materials. Many factors may affect thermal properties. This research attempts to study the effects of punch density and fiber blends on heat transfer in nonwoven. For this purpose the samples, whose properties are analyzed by using static methods for measuring their thermal conductivity, were constructed in blends of polyester with polypropylene. The blend ratios are 100% PET, 80/20, 60/40, 40/60, 20/80, and 100% PP. Six sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Experimental arrangement of the PIV measurement technique consists of (1) HiSence 12 bit digital camera, (2) light source -New-Wave Gemini pulsed laser with cylindrical optics expansion of the beam across the board cut, (3) laser beam illuminating the field of observation, (4) testing chamber, (5) textile sample, (6) heating plate, (7) thermocouples, and (8) the PC. The standard test method ASTM D7140M-13 was used.…”
Section: Fabric Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental arrangement of the PIV measurement technique consists of (1) HiSence 12 bit digital camera, (2) light source -New-Wave Gemini pulsed laser with cylindrical optics expansion of the beam across the board cut, (3) laser beam illuminating the field of observation, (4) testing chamber, (5) textile sample, (6) heating plate, (7) thermocouples, and (8) the PC. The standard test method ASTM D7140M-13 was used.…”
Section: Fabric Densitymentioning
confidence: 99%
“…These types of textiles were made directly from individualized fibres. Nonwoven fabrics are important components for good thermal insulation of the body from the surroundings and have both space and weight savings [6]. The important constructional parameters are (1) thickness, (2) weight per unit area, and (3) packing fraction, which is the ratio between the bulk density of nonwoven fabric samples and of the same sample if it was made up wholly from fibres [7].…”
Section: Introductionmentioning
confidence: 99%
“…Low price, low weight, easy production processes and diversity of structural porous properties caused nonwoven materials to be one of the most important products used for heat insulation as well. Previous studies [26,30,31,43,44,[84][85][86][87][88][89][90][91][92][93][94][95][96] evaluating nonwovens produced many different techniques indicated that fiber type, thickness, bulk density, porosity and any factors influencing these structural parameters alters the thermal insulation properties such as thermal resistance or thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%